Fresh Water Exploration in Housing Estate with Schlumberger Electrodes Geoelectric Methods - Muhammad Zuhdi; Syamsuddin Syamsuddin; Bakti Sukrisna; Agus Wachid Habiburrohman (Journal of Science and Science Education, 2022)
Geoelectricity is one of geophysical methods performed by injecting electric current into the earths. This research objected to map aquifers using geoelectric with Schlumberger electrode configuration consisting of 4 sounding points. The results are then processed with IP2WIN software which yields a real resistivity map as a function of depth. The correlation of sounding points produces three-dimensional real resistivity maps. The results of this study located at a housing estate, Mataram, West Nusa Tenggara, consists of 4 sounding points show that the aquifer is have huge amount of fresh water The aquifer layer in this area is a free aquifer. At point PA1 the depth of the aquifer starts from a depth of 81.4 – 125 meters; PA2 point at a depth of 80 – 124 meters; PA3 point at a depth of 91.8 – 118 meters; and Point PA4 at a depth of 47.4 – 113 meters